Identification of oncogenic long noncoding RNAs CASC9 and LINC00152 in oral carcinoma through genome-wide comprehensive analysis. Issue 4 (April 2019) - Chen, Mingwei; Xu, Xiaonan; Ma, Haiqing
Abstract : Oral carcinoma (OC) is the major cancer type in the head and neck region; however, the molecular mechanisms of its pathogenesis and progression remain poorly understood. In recent years, the long noncoding RNAs (lncRNAs) have been uncovered as critical regulators in the development and progression of multiple human cancers, but most of the lncRNAs expression patterns, clinical relevance, and biological functions in OC are still unclear. To better understand the significance of lncRNAs in OC carcinogenesis, we analyzed the expression levels of lncRNAs between OC and healthy oral mucosa using The Cancer Genome Atlas Cancer Genome RNA sequencing data and another three independent microarray datasets from Gene Expression Omnibus. As a result, we found that thousands of lncRNAs expression are dysregulated in OC, and further somatic copy number variation analyses showed that some of these lncRNAs alterations are associated with copy number amplification or loss in OC. Moreover, lots of lncRNAs expression levels are associated with OC patients' overall survival and recurrence-free survival; for example, higher CASC9, LINC01232, and MIR4435-1HG expression levels are related to shorter overall survival and recurrence-free survival in OC patients. Finally, the potential function of two lncRNAs (CASC9 and LINC00152) that were upregulated in OC tissues and associated with patients' survival time was verified by loss-of-function assays in OC cells. Our findings indicate that these altered lncRNAs might play important roles in the development of OC, and our data can provide a valuable list of lncRNAs candidates for further investigation of their function and mechanisms in OC. Abstract : Supplemental Digital Content is available in the text.